Reaction Pathway for Efficient Cu2ZnSnSe4 Solar Cells from Alloyed CuSn Precursor via a Cu‐Rich Selenization Stage. Issue 6 (2nd April 2020) - Pareek, Devendra; Taskesen, Teoman; Márquez, José A.; Stange, Helena; Levcenco, Sergiu; Simsek, Ibrahim; Nowak, David; Pfeiffelmann, Timo; Chen, Wenjian; Stroth, Christiane; Sayed, Mohamed H.; Mikolajczak, Ulf; et al.
Abstract : The selenization of stacked elemental metallic layers (CuSn–Zn) is a commonly reported approach in kesterite Cu2 ZnSnSe4 (CZTSe) processing. CZTSe formation via this approach usually involves a reaction route containing binary selenides, such as SnSe2− x . The high volatility of these phases at the necessary annealing temperatures (500–550 °C) makes this reaction pathway prone to Sn loss, which makes it challenging to control the composition and quality of the grown material. Herein, an approach based on stacked elemental and alloyed precursors is reported, and the benefits of using a Zn/CuSn/Zn configuration are discussed. The absence of nonalloyed elemental Sn helps in suppressing the formation and subsequent evaporation of SnSe2− x phases, preventing Sn loss from the film during selenization. This reaction pathway involves a process scheme which 1) starts with the growth of CZTSe in a "Cu‐rich" environment, 2) includes a shift of the composition by supply of SnSe2− x vapor, and 3) terminates in the "Cu‐poor" regime, leading to device efficiencies above 10%. This composition shift in the presented process appears similar to the final stage of the commonly known CIGSe three‐stage coevaporation. Abstract : Herein, a preparation route for high‐efficiency Cu2 ZnSnSe4 thin‐film solar cells is explored, which is based on as‐grown alloy precursors. It includes sputtering of precursors from mixed CuSn and elemental Zn targets and is found to prevent Sn loss during selenization. An additional Sn source is used during selenization for shifting the absorber composition from "Cu‐rich" to "Cu‐poor."